Effects of annexin A1 on apoptosis and cell cycle arrest in human leukemic cell lines - Sabran Affidah; Kumolosasi Endang; Jantan Ibrahim (Acta Pharmaceutica)
Recent studies suggest that annexin A1 (ANXA1) promotes apoptosis in cancerous cells. This study aims to investigate the effects of ANXA1 on apoptosis and cell cycle arrest in K562, Jurkat and U937 cells and peripheral blood mononu-clear cells (PBMC). Cells were treated with ANXA1 and cyclophosphamide prior to flow cytometry analysis for apoptosis and cell cycle arrest induction. At 2.5µM, ANXA1 induced significant apoptosis in K562 (p ≤ 0.001) and U937 (p ≤ 0.05) cells, with EC50 values of 3.6 and 3.8 µM, respectively. In Jurkat cells, induction was not significant (EC50, 17.0 µM). No significant apoptosis induction was observed in PBMC. ANXA1 caused cycle arrest in the G0/G1 phase in K562 and U937 cells with p ≤ 0.001 for both, and (p ≤ 0.01) for Jurkat cells. ANXA1 induced apoptosis and cycle arrest in the G0/G1 phase in K562 and U937 cells, causing only cell cycle arrest in Jurkat cells.